2012
DOI: 10.1007/s10815-012-9853-4
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases in serum and the follicular fluid of women treated by in vitro fertilization

Abstract: MMP-9 could be a good predictor of the successful IVF outcome (pregnancy), which was proven for serum as well as follicular MMP-9 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…In contrast, Lee et al found no correlation between fertilization rates and the levels of gelatinases in the follicular fluid. Although they demonstrated a significant difference between serum MMP-9 expression with implantation and pregnancy rates, as noted in previous studies, they found similar MMP-2 levels between pregnant and nonpregnant IVF-treated women [21,29,30]. They therefore suggested that MMP-9 expression in serum and in follicular fluid is essential for a successful pregnancy [30].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In contrast, Lee et al found no correlation between fertilization rates and the levels of gelatinases in the follicular fluid. Although they demonstrated a significant difference between serum MMP-9 expression with implantation and pregnancy rates, as noted in previous studies, they found similar MMP-2 levels between pregnant and nonpregnant IVF-treated women [21,29,30]. They therefore suggested that MMP-9 expression in serum and in follicular fluid is essential for a successful pregnancy [30].…”
Section: Discussionmentioning
confidence: 53%
“…In animal studies, a correlation has been noted between decreased MMP concentrations in preovulatory follicular fluid and poor oocyte release and abnormal follicular involution [21]. In addition, the presence of gelatinolytic activity at the apex of the preovulatory follicle suggests that MMPs play a role in ovulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Production of MMPs (MMP9 and MMP2) by the control and heat-stressed cumulus-oocyte complexes Because higher MMP9 levels have been associated with the developmental competence of oocytes (Robert et al 2001), implantation and pregnancy rates (Lee et al 2005, Horka et al 2012, and fertility (Dubois et al 2000), their abundance in the conditioned maturation medium (generated as a part of the transcriptome profiling efforts depicted in Fig. 1) observed after 24 h IVM in the control and heatstressed oocytes was examined.…”
Section: Heat Stress Effects On Cumulus Cellsmentioning
confidence: 99%
“…[4] showed that concentrations of proMMP9 derived from bovine cumulus-oocyte complexes after 24 hIVM were correlated with the subsequent rate of blastocyst development. Furthermore, levels of proMMP9 were greater in preovulatory follicles from which resulted successful fertilization [7], implantation and pregnancy [8, 9] of human oocytes after IVF treatment.…”
mentioning
confidence: 99%